PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI PASAR TOSS 3000 JODOH - Panjaitan, Sudirmanto Hasundungan; Pranoto, Suryo Budi (SCIENTIA JOURNAL, 2019)
Toss 3000 Jodoh Market, Batam is a traditional market that sells various household needs. Toss 3000 market has problems in product quality, price and location. To overcome problems in business that occur in the market, traders in the Toss 3000 market need to review the influence of product quality, price, and location on consumer purchasing decisions. The purpose of this study was to determine the effect of product quality, price and location on consumer purchasing decisions on the Toss 3000 Jodoh, Batam market. This research was conducted by taking a sample of 100 consumers in the Toss 3000 market who had shopped more than once. The variables used in this study are product quality (X1), price (X2) and location (X3) as independent variables and purchasing decisions (Y) as the dependent variable. The analysis technique used in this study is multiple linear regression analysis, using SPSS20 software to test the validity and reliability before each statement previously submitted is a linear regression analysis test. The results showed that product quality, price and location had a significant influence on consumer purchasing decisions.